A new gypsicultural species of Pinguicula (Lentibulariaceae), from Nuevo León, Mexico - Zamudio, Sergio; Lux, Alexander (Instituto de Ecología, A.C., 1992)
A new species of Pinguicula from gypsum soils of the state of Nuevo Leon, Mexico is described for the first time: P. immaculate subg. Temnoceras. A new locality for P. rotundiflora Studnicka is given and its type locality is corrected, which is situated in Tamaulipas, not in Oaxaca.